The Strange Story of the Second Amendment in the Federal Courts, and Why It Matters - Lee Epstein; David T. Konig (Washington University Journal of Law & Policy, 2019)
This article describes the shift in judicial interpretation of the Second Amendment. The article undertakes a statistical analysis of each of the 261 federal court decisions interpreting the Second Amendment in the decades following the Supreme Court’s first interpretation of it in 1872 and its most recent interpretations in 2008 and 2010. Until 2008, the judicial consensus was that the Second Amendment operates only to prevent the federal government from restricting firearms possession. The article traces the ascendance in recent decades of the view that the amendment actually protects an individual right against infringement by either the state or federal government. The article then assesses various arguments about the practical importance of this shift, and considers potential avenues for proponents of stronger gun control to counteract this recent shift.
Keywords: second amendment; federal courts; gun control; Supreme Court